ORGANIZATION OF THE TEACHING DISCIPLINE OF ELECTRICAL ENGINEERING AND ELECTRONICS FUNDAMENTALS ON THE BASIS OF MODERN EDUCATIONAL TECHNOLOGIES IS AN IMPORTANT FACTOR IN THE TRAINING OF COMPETITIVE PERSONNEL (Proceedings of International Educators Conference, 2024)
This article analyzes the current state of the organization of training in the field of Electrical engineering and electronics fundamentals. It is also noted that the development of the quality of the trained personnel is one of the important tasks of the educational system. It was mentioned that the organization on the basis of modern technologies and, through this, the goal of independent fixation and creative abilities of the educational community was achieved.